Effects of fasting on tissue glucose utilization in conscious resting rats. Major glucose-sparing effect in working muscles. - Issad, T (1987)
The effects of fasting on glucose metabolism in the conscious resting rat were studied. Fasting decreased whole-body glucose utilization by 40%. The fast induced a decrease in glucose utilization in muscles which are constantly working even in the resting state, i.e. heart, diaphragm and postural muscles. No modification was observed in other tissues.